2012
DOI: 10.1155/2012/973974
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life among Patients with Coronary Artery Disease: A Post-Treatment Follow-Up Study in Iran

Abstract: Objective. To examine the changes in health-related quality of life (HRQoL) in patients with coronary artery disease (CAD) in terms of age, gender, and treatment strategy in Iran. Methods and Materials. Forty-nine patients responded to the Iranian version of the 36-item short form (SF-36) questionnaire to evaluate the HRQoL at first and third year after treatment. The paired and independent Wilcoxon rank-sum tests were used for within and between comparisons, respectively. Multivariate regression analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
2
17
1
Order By: Relevance
“…However, it is in contrast to the results reported by Taheri, revealing a relationship between QoL, and sex and marital status (18). On the other hand, Tofighi et al reported no significant relationships between the score of QoL and intervention type, which is on the contrary to the findings of the current research that indicated intervention type as the only effective factor in changing the CAD patients' QoL (14). The results of the present research disclosed that the patients' QoL was significantly different before and after the intervention via CABG and PCI, and significantly increased after the intervention.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, it is in contrast to the results reported by Taheri, revealing a relationship between QoL, and sex and marital status (18). On the other hand, Tofighi et al reported no significant relationships between the score of QoL and intervention type, which is on the contrary to the findings of the current research that indicated intervention type as the only effective factor in changing the CAD patients' QoL (14). The results of the present research disclosed that the patients' QoL was significantly different before and after the intervention via CABG and PCI, and significantly increased after the intervention.…”
Section: Discussioncontrasting
confidence: 99%
“…This implies that there were no significant relationships between demographic variables and change in the score of QoL (Tables 1 and 2). This finding is consistent with that of the study by Tofighi et al, which indicated no significant relationships between changes in the score of QoL, and age and sex (14). However, it is in contrast to the results reported by Taheri, revealing a relationship between QoL, and sex and marital status (18).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Tofighi et al showed a study in Iran hospital that disturbed HRQOL of CHD was increased with older age, was reduced with higher levels of education and income, and was elevated among women than men. 7 In this study we found that service holders and businessmen were always in sedentary life style, taken high cholesterol diet with reduced physical exercise, so they were more affected by CHD whereas day laborer, farmer were hard worker. Also housewives were hard worker, so they were less affected.…”
Section: Discussionmentioning
confidence: 68%
“…In a study by Tofighi et al (15), health status of CAD patients after CABG and PCI has been reported with a 3 years follow-up. The MacNew consists of twenty-seven questions that inquire about symptoms like: angina/chest pain, shortness of breath, fatigue, dizziness, and aching legs and finally summarized into three main domains, emotional, physical, and social well-being.…”
Section: Effectivenessmentioning
confidence: 99%